Probe design for mining and selection of genes coding endo 1- 4 xylanase from dna metagenome data - Huyen, Do Thi; Giang, Nguyen Minh; Nguyet, Nguyen Thu; Hai, Truong Nam (Academia Journal of Biology, 2018)
According to the CAZY classification, endo 1- 4 xylanase belongs to GH 5, 8, 10, 11, 30, 51, 98. However only 03 sequences of GH8, 27 sequences of GH10, 18 sequence of GH11, only one sequence of each GH30 and GH51 from CAZy and NCBI database were thouroughly experimentally studied for biological activity and characteristics of the enzyme. Through the collected sequences, two probes for endo 1- 4 xylanase of GH10 and GH11 were designed, based on the sequence homology. The GH10 probe was 338 amino acids lenghth contained all the conserved amino acid residues (16 conserved residues in all sequences, 13 residues similar in almost sequences, 14 residues conserved in many sequences) with the lowest maxscore of 189, coverage of 88% and identity of 39%. The GH11 probe was 204 amino acids contained all the conserved amino acid residues (54 conserved residues were identity in all sequences, 25 residues similar in almost sequences, 24 residues conserved in many sequences) with the lowest maxscore of 165, coverage of 84% and identity of 50%. Using the two probes, we mined only one sequence (GL0018509) for endo 1- 4 xylanase from metagenomic DNA data of free-living bacteria in Coptotermes termite gut. Prediction of three-dimention structure of GL0018509 sequence by Phyre2 and Swiss Prot showed that this sequence was high similarity (95% by Phyre2 and 93,4% by Swiss Prot) with endo 1- 4 xylanase with the 100% confidence.